Sex-dependent regulation of retinal pigment epithelium and retinal function by Pgc-1α - Taskintuna, Kaan; Bhat, Mohd Akbar; Shaikh, Tasneem; Hum, Jacob; Golestaneh, Nady (Frontiers in Cellular Neuroscience, 2024)
Age-related macular degeneration (AMD) is a major cause of blindness that affects people over 60. While aging is the prominent factor in AMD, studies have reported a higher prevalence of AMD in women compared to age-matched men. Higher levels of the innate immune response's effector proteins complement factor B and factor I were also found in females compared to males in intermediate AMD. However, the mechanisms underlying these differences remain elusive. Peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) is a key regulator of mitochondrial biogenesis and metabolic pathways. Previously, we showed that Pgc-1α repression and high-fat diet induce drastic AMD-like phenotypes in mice. Our recent data revealed that Pgc-1α repression alone can also induce retinal pigment epithelium (RPE) and retinal dysfunction in mice, and its inhibition in vitro results in lipid droplet accumulation in human RPE. Whether sex is a contributing factor in these phenotypes remains to be elucidated. Using electroretinography, we demonstrate that sex could influence the RPE function during aging independent of Pgc-1α in wild-type (WT) mice. We further show that Pgc-1α repression exacerbates RPE and retinal functions in females compared to aged-match male mice. Gene expression analyses revealed that Pgc-1α differentially regulates antioxidant enzymes and mitochondrial dynamic genes in males and females. RPE flat mounts immunolabeled with TOMM20 and DRP1 indicated a sex-dependent role for Pgc-1α in regulating mitochondrial fission.Analyses of mitochondrial network morphology suggested sex-dependent effects of Pgc-1α repression on mitochondrial dynamics.Together, our study demonstrates that inhibition of Pgc-1α induces a sex-dependent decline in RPE and retinal function in mice. These observations on the sex-dependent regulation of RPE and retinal function could offer novel insights into targeted therapeutic approaches for age-related RPE and retinal degeneration.